1998
DOI: 10.1016/s0896-6273(00)80543-7
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutation in trkB Causes Loss of NT4-Dependent Neurons without Major Effects on Diverse BDNF Responses

Abstract: Neurotrophins are a family of soluble ligands that promote the survival and differentiation of peripheral and central neurons and regulate synaptic function. The two neurotrophins, brain-derived neurotrophic factor (BDNF) and neurotrophin-4 (NT4), bind and activate a single high-affinity receptor, TrkB. Experiments in cell culture have revealed that an intact Shc adaptor binding site on TrkB and subsequent activation of the Ras/MAPK pathway are important for neuronal survival and neurite outgrowth. To elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
147
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(154 citation statements)
references
References 62 publications
6
147
1
Order By: Relevance
“…For example, in TrkA, the receptor for nerve growth factor, phosphorylation of a juxtamembrane tyrosine leads to Ras and PI3-kinase activation, which are important for cell survival and neurite outgrowth (Greene and Kaplan, 1995;Huang and Reichardt, 2001), whereas phosphorylation of a tyrosine in the C-terminal region of TrkA leads to PLCγ activation, which is crucial for NGF-dependent Na + channel and VRI channel regulation (Choi et al, 2001;Chuang et al, 2001). Moreover, in TrkB, phosphorylation of a single juxtamembrane tyrosine is required for nearly all of NT4-dependent signaling whereas phosphorylation of other tyrosine residues are required to mediate BDNF-dependent signaling in vivo (Minichiello et al, 1998). Similarly, in Met, the receptor for hepatocyte growth factor, a binding site for Grb2 is essential for late steps in myogenesis (Maina et al, 1996), a binding-site for PI3-kinase is essential for placental development, hepatocyte survival and myoblast migration, and a Src binding-site is essential for motor axon outgrowth (Maina et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in TrkA, the receptor for nerve growth factor, phosphorylation of a juxtamembrane tyrosine leads to Ras and PI3-kinase activation, which are important for cell survival and neurite outgrowth (Greene and Kaplan, 1995;Huang and Reichardt, 2001), whereas phosphorylation of a tyrosine in the C-terminal region of TrkA leads to PLCγ activation, which is crucial for NGF-dependent Na + channel and VRI channel regulation (Choi et al, 2001;Chuang et al, 2001). Moreover, in TrkB, phosphorylation of a single juxtamembrane tyrosine is required for nearly all of NT4-dependent signaling whereas phosphorylation of other tyrosine residues are required to mediate BDNF-dependent signaling in vivo (Minichiello et al, 1998). Similarly, in Met, the receptor for hepatocyte growth factor, a binding site for Grb2 is essential for late steps in myogenesis (Maina et al, 1996), a binding-site for PI3-kinase is essential for placental development, hepatocyte survival and myoblast migration, and a Src binding-site is essential for motor axon outgrowth (Maina et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The NT-4/5 gene codes for a 26-kDa homodimeric protein of 123 amino acids, sharing 54% homology with BDNF (Ip et al, 1992, Ibanez, 1996, Salin et al, 1997. Although NT-4/5 and BDNF are both highaffinity ligands for the TrkB receptor, the two neurotrophins have distinct biological activities in the nervous system (Klein et al, 1992, Curtis et al, 1995, McAllister et al, 1995, Ryden et al, 1995, Strohmaier et al, 1996, Minichiello et al, 1998, and some populations of neurons require NT-4/5 but not BDNF for survival (Ardelt et al, 1994, Conover et al, 1995, Liu et al, 1995, Riddle et al, 1995. Furthermore, replacing the spatio-temporal expression pattern of BDNF with NT4/5 by 'knocking-in' NT4/5 to the BDNF locus does not rescue all of the deficits, providing direct evidence that the two neurotrophins have some non-overlapping actions (Fan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, infusion of NT-4/5 but not BDNF is neuroprotective after LFP-TBI (Blaha et al, 2000, Royo et al, 2006. The mechanisms for this difference may include partially different binding sites on the trkB receptor (Klein et al, 1992), differential activation of a particular shc domain on the cytoplasmic portion of the trkB receptor (Minichiello et al, 1998), and/or differential downregulation of trkB (Frank et al, 1996, Knusel et al, 1997). …”
Section: Discussionmentioning
confidence: 99%
“…[75] NT-4 is synthesized by DRG and expressed in the rat spinal cord. [76] It is a ligand of the TrkB tyrosine kinase receptor, but it mediates to diverse effects in relation to BDNF. [74] It has also been demonstrated that repeated injections of a specific antibody to NT-4 failed to reverse the thermal hyperalgesia caused by sciatic nerve ligation in mice.…”
Section: Neurotrophins and Nerve Growth Factorsmentioning
confidence: 99%
“…[74] It has also been demonstrated that repeated injections of a specific antibody to NT-4 failed to reverse the thermal hyperalgesia caused by sciatic nerve ligation in mice. [76] Glial cell line-derived neurotrophic factor (GDNF) has been shown to prevent and reverse sensory abnormalities that developed in various NP models, without affecting pain-related behavior. GDNF reduces ectopic discharges within sensory neurons after nerve injury and this effect may involve modulation of sodium channels.…”
Section: Neurotrophins and Nerve Growth Factorsmentioning
confidence: 99%